P514Towards cell-specific targeting of proteasomes in vascular cells. (15th July 2014) - Wieber, S; Florea, BI; Wagner, AH; Overkleeft, HS; Hecker, M; Drews, O
Abstract: Introduction: Within the past decade, it has been demonstrated that the outcome of multiple cardiovascular diseases can be modulated via the proteasome, which is already a target of cancer chemotherapeutics. However, the proteasome is a heterogenous group of multi-protein complexes and their precise assembly in vascular cells remains unknown. Therefrore, aim of the study was to map the functional subproteome of 20S proteasome complexes in vascular cells in detail. Methods and Results: Proteasome complexes of cell lysates as well as intact cells were analyzed based on the covalent binding of fluorescent inhibitors, which target only active proteolytic subunits in fully assembled 20S proteasomes. Application of both approaches revealed the existence of an unanticipated proteasome heterogeneity in human vascular and blood-derived cells with a mixed assembly of constitutive and inducible proteasomal subunits even under baseline conditions. Remarkably, the ratio of constitutive to inducible proteasomal subunits allowed to differentiate between the cells. The results obtained via living cell targeting showed that the highest abundance of functional, inducible subunits exists in lymphocytes (LC) and monocytes (MC) followed by platelets (Plt) and endothelial cells (EC), and was minimal in smooth muscle cells (SMC) (e.g. subunit β5i +50% in MC vs. EC, +90% in MC vs. SMC, p<0.01, n=4-8). On the other hand, the functional constitutive counterparts of the inducible proteolytic subunits were most abundant in EC and least abundant in Plt (e.g. subunit β5 +75% in EC vs. MC, +85% in EC vs. LC, + 90% in EC vs. Plt, p<0.01, n=4-8). Notably, the overall abundance of functional proteasome complexes was cell-type dependent as well. Thus, incorporation of proteolytic subunits in active 20S proteasomes was a function of subunits targeted by the fluorescent inhibitors and proteasome concentration in the cell. To validate the results obtained for EC and SMC under cell culture conditions, murine aortae were perfused with the fluorescent inhibitors. Fluorescence microscopy confirmed tissue penetration of the fluorescent inhibitors into the intima, media and adventitia, thus enabling a highly specific staining of active proteolytic subunits of the proteasome, whereby the proteasome assembly in the tissue matched that of cultured cells. Conclusion: Proteasome assembly is characteristic among vascular cells predicting an opportunity for a cell-directed proteasome targeting not only in the pathology of blood-borne cancer, but also in cardiovascular disorders.